Discovery of Osmotic Responses of Sweet Potato Meristems in Cryoprotective Solutions - Shevchenko, Nadiya; Kovalenko, Galyna; Kovalenko, Igor; Stribul, Tamara (Problems of Cryobiology and Cryomedicine, 2021)
Probl Cryobiol Cryomed 2021; 31(2): 180–184